Femoroacetabular impingement in young adults: assessment and management. (2nd October 2019) - Matar, Hosam E; Rajpura, Asim; Board, Tim N
Abstract : Femoroacetabular impingement is a cause of hip pain in young adults as a result of premature dynamic contact between the femur and acetabulum that occurs within the physiological range of hip motion. Diagnosis is made by patient history, clinical examination and radiographic findings. Cross-sectional imaging with computed tomography and magnetic resonance arthrography may be necessary in selected patients. Femoroacetabular impingement can be treated non-operatively with physiotherapist-led conservative care including analgesia and intra-articular steroid injections. Arthroscopic hip surgery aiming to restore pain-free functional range of movement and repair damaged labrum can help in selected patients with no pre-existing osteoarthritis. This review outlines the clinical assessment, investigations and management of femoroacetabular impingement in young adults.